The cultural identity of white Afrikaner women: a post- Jungian perspective - Griessel, Loura; Kotzé, Martina (University of the Free State, 2010)
A post-Jungian model of the development of the self (Hill 1992) is used to analyse how the female Afrikaner identity became embedded in the South African social and political contexts. It is argued with Jungian concepts that, because of their history and culture, Afrikaner women grew up amid a cultural identity that became entrenched in the static Masculine and a patrivalent culture pattern. Consequently, for most of the twentieth century, Afrikaner women as a group were prone to function as Father’s Daughters, with a strong constellation of the archetypal image of Amazon and its patterns of Martyr and Dutiful Daughter. Some implications for the development of the self in these women are then discussed.

’n Post-Jungiaanse model van die ontwikkeling van die self (Hill 1992) is gebruik om te analiseer hoe die vroulike Afrikaner-identiteit ingebed geraak het binne die Suid-Afrikaanse sosiale en politieke kontekste. In Jungiaanse terme het Afrikanervroue hoofsaaklik opgegroei binne ’n kulturele identiteit wat onderlê is deur die “statiese Manlikheid” en ’n patriargale kulturele patroon. As uitvloeisel hiervan het Afrikanervroue as ’n groep, tydens die grootste gedeelte van die twintigste eeu, as “Vader se Dogters” gefunksioneer, met ’n sterk konstellasie van die argetipiese beeld van Amasone en die gepaardgaande patrone van “Martelaar” en “Pligsgetroue Dogter”. Implikasies vir die ontwikkeling van die self in hierdie vroue word ook kortliks bespreek.
Keywords: Afrikaners; Development of the self; Women